Efficacy and Safety of Glutamine-supplemented Parenteral Nutrition in Surgical ICU Patients: An American Multicenter Randomized Controlled Trial. Issue 4 (April 2016) - Ziegler, Thomas R.; May, Addison K.; Hebbar, Gautam; Easley, Kirk A.; Griffith, Daniel P.; Dave, Nisha; Collier, Bryan R.; Cotsonis, George A.; Hao, Li; Leong, Traci; Manatunga, Amita K.; Rosenberg, Eli S.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To determine whether glutamine (GLN)-supplemented parenteral nutrition (PN) improves clinical outcomes in surgical intensive care unit (SICU) patients. Summary Background Data: GLN requirements may increase with critical illness. GLN-supplemented PN may improve clinical outcomes in SICU patients. Methods: A parallel-group, multicenter, double-blind, randomized, controlled clinical trial in 150 adults after gastrointestinal, vascular, or cardiac surgery requiring PN and SICU care. Patients were without significant renal or hepatic failure or shock at entry. All received isonitrogenous, isocaloric PN [1.5 g/kg/d amino acids (AAs) and energy at 1.3× estimated basal energy expenditure]. Controls (n = 75) received standard GLN-free PN (STD-PN); the GLN group (n = 75) received PN containing alanyl-GLN dipeptide (0.5 g/kg/d), proportionally replacing AA in PN (GLN-PN). Enteral nutrition (EN) was advanced and PN weaned as indicated. Hospital mortality and infections were primary endpoints. Results: Baseline characteristics, days on study PN and daily macronutrient intakes via PN and EN, were similar between groups. There were 11 hospital deaths (14.7%) in the GLN-PN group and 13 deaths in the STD-PN group (17.3%; difference, −2.6%; 95% confidence interval, −14.6% to 9.3%; P  = 0.66). The 6-month cumulative mortality was 31.4% in the GLN-PN group and 29.7% in the STD-PN group ( P  = 0.88). Incident bloodstream infection rate was 9.6 and 8.4 per 1000 hospital days in the GLN-PN and STD-PN groups, respectively ( P  = 0.73). Other clinical outcomes and adverse events were similar. Conclusions: PN supplemented with GLN dipeptide was safe, but did not alter clinical outcomes among SICU patients.